IDENTIFIKASI BULL AND BEAR MARKET DI PASAR MODAL SYARIAH INDONESIA: PENDEKATAN MARKOV-SWITCHING [IDENTIFICATION OF THE BULL AND BEAR MARKET IN THE INDONESIAN SHARIA CAPITAL MARKET: THE MARKOV-SWITCHING APPROACH] - Arief Surya Lesmana (Universitas Pelita Harapan, 2023)
The development of the Indonesian Islamic capital market cannot be separated from the bullish and bearish phenomena. Bullish and bearish conditions need special attention because they will affect investors’ decisions in buying, holding, or selling shares. This study aims to identify bullish and bearish conditions in the Indonesian Islamic capital market based on ISSI and JII data from January 2012 to December 2022. This study uses a quantitative approach with the Markov-Switching model technique. The result shows that in bullish conditions, ISSI can provide a return of 1.21% with a risk of 0.02%, while in bearish conditions ISSI can provide a return of -1.49% with a risk of 0.12%. Identification results on the ISSI data show that there were 101 bullish months with an expected duration of 9.5 months and 31 bearish months with an expected duration of 4.02 months. In addition, in bullish conditions, JII is able to provide a return of 0.17% with a risk of 0.02%, while in bearish conditions, JII can provide a return of -1.65% with a risk of 0.13%. Identification results on the JII data show that there were 90 bullish months with an expected duration of 5.93 months and 42 bearish months with an expected duration of 3.98 months.Abstrak dalam Bahasa Indonesia. Perkembangan pasar modal syariah Indonesia tidak terlepas dari fenomena bullish dan bearish. Kondisi bullish dan bearish perlu mendapat perhatian khusus karena dapat mempengaruhi keputusan investor dalam pembelian, penahanan, atau penjualan saham. Penelitian ini bertujuan untuk mengidentifikasi kondisi bullish dan bearish di pasar modal syariah Indonesia berdasarkan data ISSI dan JII periode Januari 2012 hingga Desember 2022. Penelitian ini menggunakan pendekatan kuantitatif dengan Markov-Switching Model. Hasil penelitian menunjukkan bahwa pada kondisi bullish ISSI dapat memberikan tingkat pengembalian 1,21% dengan risiko 0,02%, sedangkan pada kondisi bearish ISSI dapat memberikan tingkat pengembalian -1,49% dengan risiko 0,12%. Pada data ISSI ditemukan 101 bulan bullish dengan rata-rata durasi 9,5 bulan dan 31 bulan bearish dengan rata-rata durasi 4,02 bulan. Selain itu pada kondisi bullish JII mampu memberikan tingkat pengembalian 0,17% dengan risiko 0,02%, sedangkan pada kondisi bearish, JII mampu memberikan tingkat pengembalian -1,65% dengan risiko 0,13%. Pada data JII ditemukan 90 bulan bullish dengan rata-rata durasi 5,93 bulan dan 42 bulan bearish dengan rata-rata durasi 3,98 bulan.